2014
DOI: 10.5897/jssem13.0413
|View full text |Cite
|
Sign up to set email alerts
|

The influences of forest fire on the vegetation and some soil properties of a savanna ecosystem in Nigeria

Abstract: The effect of forest fire on natural forest in Southern Guinea Savanna in Nigeria was investigated. The study was carried out in Oro forest reserve in Kwara State, Nigeria. The study site was located in the north-eastern and south-western portions of the reserve. In each location in the forest, one hectare (100 m × 100 m) was divided into 100 plots of 10 m × 10 m. Twenty plots were randomly selected for determining the frequency of burned trees, re-sprouted trees and the numbers of seedling/ha. Soil samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…This study revealed that rainfall reduced the concentration of Na and Mg in the soils. This observation is in alignment with the findings of Olujugba and Fatubarin, [25], who postulated that high precipitation might lead to decrease in exchangeable bases. This implies that seasonal variation has affected the content of exchangeable bases in the three-land use types.…”
Section: Soil Chemical Propertiessupporting
confidence: 92%
“…This study revealed that rainfall reduced the concentration of Na and Mg in the soils. This observation is in alignment with the findings of Olujugba and Fatubarin, [25], who postulated that high precipitation might lead to decrease in exchangeable bases. This implies that seasonal variation has affected the content of exchangeable bases in the three-land use types.…”
Section: Soil Chemical Propertiessupporting
confidence: 92%
“…Only at higher temperatures can forest fires considerably raise the soil pH from 5 to 6.3 at depths of 0 to 10 cm and 5.7 to 6.2 at depths of 11 to 20 cm depth [32]. The high pH of the ash may raise the soil pH.…”
Section: Soil Ph and Ecmentioning
confidence: 99%
“…Nigerian soil is lateritic in nature (red soil) and can easily be wash away as a result of flooding activities. Soil erosion has made the soil not good for agricultural purpose [2][3][4][5][6]. Hence, farmers depend on fertilizers produces from inorganic industrial processes that are not only costly but harmful to our environment in the long run [7].…”
Section: Introductionmentioning
confidence: 99%